Method of increasing the longitudnal current of Н⁻ ions from pig with a metal-hydride cathode - Sereda, I.N.; Tseluyko, A.F.; Ryabchikov, D.L.; Hrechko, Ya.O.; Krupka, A.A. (Вопросы атомной науки и техники, 2019)
The possibility of increasing the current of negative hydrogen ions extracted in the longitudinal direction from Penning discharge with a metal-hydride cathode by changing potentials at the discharge cathodes is investigated. An electromagnetic filter is used to separate negative ions from the extracted flux of charged particles. A significant correlation between the extracted total current and the current of negative ions from the cathode potential was found. The optimal parameters for the effective extraction of H⁻ ions are determined. The current of the H⁻ ion beam at a level of 10 μA was obtained.